Review and analysis of land use change models and future scenarios studies - Gallardo, Marta (Geographicalia, 2018)
In the last decades there has been a broad development of techniques and models to capture and analyze land use dynamics, at global, regional, national and local scales. This interest is shown in the several institutional programs and studies that have been carried out with the main purpose of assessing and addressing a sustainable development of the territory. Sustainability has very different implications, so these studies are also wide-ranging depending on their objective. Models have become more complex, from simple extrapolations to statistical-mathematical models that compile different techniques. A review of different land use change and future scenarios works is presented, describing different typologies, methodologies, driving factors and models used, worldwide and in Spain. Finally, themain problems and challenges faced by this subject are presented.